Time-Resolved Analysis of Candidate Gene Expression and Ambient Temperature During Bud Dormancy in Apple - Lempe, Janne; Peil, Andreas; Flachowsky, Henryk (Frontiers in Plant Science, 2022)
Winter dormancy – a period of low metabolic activity and no visible growth - appears as adaptation to harsh winter conditions and can be divided into different phases. It is tightly controlled by environmental cues, with ambient temperature playing a major role. During endodormancy, a cultivar specific amount of cold needs to be perceived, and during ecodormancy, heat hours accumulate before bud burst and anthesis in spring. Expression analysis, performed in several key fruit tree species, proved to be very useful in elucidating the molecular control of onset and release of dormancy. The time resolution of these experiments however has been limited. Therefore, a dense time series expression analysis was conducted here for 40 candidate genes involved in dormancy control, under the cool-temperate climate conditions of Dresden. Samples were taken of the cultivars ‘Pinova’ and ‘Gala’, which differ in flowering time. The set of candidate genes included well-established dormancy genes like DAM genes, MdFLC-like, ICE1, PRE 1 and MdPIF4. Furthermore, we tested genes from dormancy-associated pathways including the brassinosteroid, gibberellic acid, abscisic acid, cytokinin response and respiratory stress pathways. The expression patterns of well-established dormancy genes were confirmed and could be associated with specific dormancy phases. In addition, less well-known transcription factors and genes of the ABA signaling pathway showed associations with dormancy progression. The three ABA signaling genes HAB1_chr15, HAI3 and ABF2 showed a local minimum of gene expression in proximity of the endo- to ecodormancy transition. The number of sampling points allowed us to correlate expression values with temperature data, which revealed significant correlations of ambient temperature with expression of the M. domestica genes MdICE1, MdPIF4, MdFLC-like, HAB1_chr15, and the Type-B cytokinin response regulators BRR9. Interestingly, the slope of the linear correlation of temperature with expression of MdPIF4 differed between cultivars. Whether the strength of inducibility of MdPIF4 expression by low temperature differs between the ‘Pinova’ and ‘Gala’ alleles, needs to be tested further.